PENGARUH PENDAPATAN ASLI DAERAH DAN BELANJA MODAL TERHADAP KEMANDIRIAN KEUANGAN DAERAH PADA KABUPATEN/KOTA DI PROVINSI SUMATERA BARAT TAHUN 2016 -2021 - Muhammad Rivandi; Yeyen Anggraini (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to see the effect of the influence of regional original income and capital expenditure on regional financial independence in districts/cities in the province of West Sumatra. This study has a population of 19 regencies and cities in the province of West Sumatra. This study uses the Total Sampling technique. The data used is secondary data obtained from www.djpk.kemenkeu.go.id. The method used in this study is multiple regression of panel data with the help of the E-Views 10 program. The results of this study indicate that the Regional Original Income variable has a significant positive effect on Regional Financial Independence partially. Then, the Capital Expenditure variable has a significant positive effect on Regional Financial Independence partially.